Cultural awareness in the Malaysian ESL literature classroom / Siti Hajar Aishah Mohd Azkah - Mohd Azkah, Siti Hajar Aishah (2013)
This study was conducted with the aim to investigate cultural awareness in the Malaysian ESL literature classroom. The descriptive study comprised 30 ESL teachers from 6 public secondary schools from Selangor and Kelantan. The study employed a mixed-methods research design where data were collected using a questionnaire and semi-structured interviews. The quantitative data were statistically analysed using SPSS version 20 while the qualitative data were analysed using thematic analysis to trace emerging themes. The validity and reliability of instruments were established through experts‟ opinions and a pilot study. The overall reliability was established at 0.887 alpha level. The findings revealed that teachers think cultural content in the current literary texts is suitable. However, the integration of cultural awareness was at a minimal level. Teachers highlighted that they were not trained and it was not a tested component in the major public examinations. Among challenges faced are students‟ low proficiency of English, followed by students‟ and teachers‟ lack of cultural knowledge, students‟ negative perceptions and lastly, time constraint. The findings imply that the integration of cultural awareness in the Malaysian ESL literature classroom leaves much to be desired. Therefore, more local texts reflecting Malaysian diverse ethnic groups ought to be included in the KBSM English Literature Component. More importantly, the Ministry of Education (MOE) needs to provide appropriate training and teaching and learning materials to help teachers address cultural awareness. Such a move may serve as a platform to improve the integration of cultural awareness in the Malaysian ESL literature classroom